2015
DOI: 10.1097/ta.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

The safety of early fresh, whole blood transfusion among severely battle injured at US Marine Corps forward surgical care facilities in Afghanistan

Abstract: Therapy study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…The studies conducted in the military setting included Auten et al, 24 Keneally et al, 25 Nessen et al, 26 Perkins et al, 27 and Spinella et al 28 . Auten et al, 24 Keneally et al, 25 Nessen et al, 26 and Spinella et al 28 . reported on the use of either fresh whole blood or warm fresh whole blood in combination with component therapy as an intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies conducted in the military setting included Auten et al, 24 Keneally et al, 25 Nessen et al, 26 Perkins et al, 27 and Spinella et al 28 . Auten et al, 24 Keneally et al, 25 Nessen et al, 26 and Spinella et al 28 . reported on the use of either fresh whole blood or warm fresh whole blood in combination with component therapy as an intervention.…”
Section: Resultsmentioning
confidence: 99%
“…reported on the use of either fresh whole blood or warm fresh whole blood in combination with component therapy as an intervention. The Auten et al, 24 Keneally et al, 25 and Nessen et al 26 studies performed a propensity score adjusted logistic regression analysis, whereas Spinella et al 28 . compared cohorts via a multivariable logistic regression.…”
Section: Resultsmentioning
confidence: 99%
“…In a multivariate analysis, Spinella et al found that fresh whole blood recipients had improved 24‐hour and 30‐day survival compared to those who received only component therapy . Auten et al and Perkins et al showed that while recipients of fresh whole blood tended to have more severe injuries than component therapy recipients, both groups had similar mortality rates at 24 hours and 30 days …”
Section: Resultsmentioning
confidence: 99%
“…However, by the very nature of the environment, the effect may be more difficult to prove. Up to now, all data on WB in RDCR are retrospective and may well be misleading . HEH further reminded the audience of the paper by John Ioannidis (“Why most published research findings are false”), who warned that “the hotter the scientific field (with more scientific teams involved), the less likely the research findings are to be true.” HEH therefore concluded that although WB provides blood cells in a smaller volume and with lesser anticoagulant than does component therapy, the clinical advantage of WB over component therapy protocols may prove impossible to show scientifically.…”
Section: Nato Blood Panelmentioning
confidence: 99%